ANALISIS PERBANDINGAN MAKNA MUSIM DALAM PERIBAHASA MANDARIN DAN PERIBAHASA INDONESIA - Jaya, William Septia; Thamrin, Lily; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Proverbs are one of our forms of expression.proverbs use a variety of elements, one of which is the element of seasons. Seasons are an inseparable part of everyday life, because seasons have a great influence on people's lives. Seasons in different regions make people's expressions and thoughts also different. Because China and Indonesia have different people's cultural backgrounds, thoughts and living habits, the people of the two countries also have differences in observation and introduction to the seasons. The author hopes that through the comparison of Chinese and Indonesian season proverbs, it can increase students' knowledge and mastery of proverbs. Therefore, the author chose the title of comparative analysis of the meaning of seasons in Mandarin proverbs and Indonesian proverbs as research. Through literature analysis and comparative analysis methods, the author collected 83 Chinese season proverbs and 29 Indonesian season proverbs. Chinese season proverbs containing positive meanings are 37.35% with a total number of proverbs that are 31 pieces, neutral meanings are 56.63% with a total number of proverbs that are 47 pieces, negative meanings are 6.02% with a total number of proverbs that are 5 pieces. In the Indonesian season proverbs that contain positive meanings there are 10.34% with a total number of proverbs that are 3 pieces, neutral meanings are 68.97% with a total number of proverbs that are 20 pieces, negative meanings are 20.69% with a total number of proverbs that are 6 pieces.